MCFC fed with biogas: Experimental investigation of sulphur poisoning using impedance spectroscopy - Cigolotti, Viviana; McPhail, Stephen; Moreno, Angelo; Yoon, Sung Pil; Han, Jong Hee; Nam, Suk Woo; Lim, Tae-Hoon (PERGAMON-ELSEVIER SCIENCE LTD, 2011)
The combination of biogas from anaerobic digestion and molten carbonate fuel cell (MCFC) enables highly efficient utilisation of a renewable energy source, maximizing the energetic yield from alternative fuels and minimizing environmental impact in terms of polluting emissions. However, the contaminant levels in the biogas are often unacceptable for performing and durable operation of an MCFC; it is thus desirable to establish and improve the tolerance level of the fuel cell to these contaminants. In this work, the effect of hydrogen sulphide (H2S) in the fuel gas is investigated on the electrochemical performance and the regenerative capacities of a single MCFC. Different concentrations of H2S (1, 3, 5, 8 ppm) were added to the anode gas composition during cell operation and the respective effects are investigated. Electrochemical impedance measurements are carried out to identify the processes which take place in the anode. Experimental results will be presented, showing the effects and implications of cell poisoning with H2S, the most common contaminant from biogas produced by anaerobic digestion, harmful to both the MCFC anode and the reforming catalyst. This investigation is required in order to identify the tolerance limits of current MCFC materials, especially as regards different concentrations of H2S that can occur due to composition variations of the produced biogas. Copyright (C) 2010, Hydrogen Energy Publications, LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: FUEL; H2S